(untitled) (Jurnal Peternakan Lingkungan Tropis, 2023)
The study aims to determine the uses of fibercreme as a substitute for coconut milk with different concentrations on the analysis of fat content and organoleptic acceptability of rendang. The study used a completely randomized design with four treatments and five replications. The data obtained was analyzed using variance (ANOVA) to determine differences between treatments and further analyzed using Duncan’s Multiple Range Test (DMRT). The study showed that the treatment of using fibercreme as a substitute for coconut milk with different concentrations in rendang had no significant effect on the color test for the brightness value of L*, had a significant effect on the redness of a*, and had no significant effect on the value of yellowness of b*. The results of the study showed that the organoleptic quality was significantly different (P<0.05) on the hedonic color and taste scale, and was not significantly different in aroma and texture while the hedonic quality was significantly different in color and texture, and not significantly different in aroma and taste. The fat content test using Soxhlet extraction showed significantly different results. The highest fat content was found in P3 while the lowest fat content was found in P1.